Single nucleotide polymorphism (g.2786 A>G) of DGAT1 gene associated with milk yield and fat percentage in crossbred cattle - SINGH, AKANSHA; KUMAR, AMIT; PATEL, JYOTI; CHAUDHARY, RAJNI; JADHAV, S E; MAURYA, V P; MISHRA, B P; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
In present study, association of five single nucleotide polymorphisms (SNPs) of database rs109421300, rs43691049, rs109727821, rs109047657 and rs135678421 was investigated with milk minerals including calcium (Ca), phosphorus (P), copper (Cu), zinc (Zn), manganese (Mn), iron (Fe), sodium (Na), potassium (K) and constituents (fat and protein percentage) after adjusting the records with various significant non-genetic factors in crossbred (Vrindavani) cattle. The effect of rs109421300 pertaining to Diacylglycerol Acyltransferase (DGAT) gene located on BTA 14, was highly significant on fat percentage and significant on test day milk yield and non-significant on Ca, Cu, Mn, Zn, Fe, Na, K, test day milk yield and protein percentage. The AA genotypes of rs109421300 locus had significantly lower (2.96±0.17%) fat percentage than AG (4.64±0.22%), GG (4.62±0.27%) genotypes but simultaneously cows with AA genotypes had significantly highest (11.59±0.51 kg) test day milk yield than other two genotypes. At locus rs109727821, the manganese concentration was significantly highest (1.64±0.16 mg/l) for AG followed by AA (0.98±0.15 mg/l) and GG (0.77±0.24 mg/l) genotypes. The other SNPs had no significant association with traits under investigation. The existing association suggested possibilities to select animals for specific minerals and constituent traits in crossbred population.